2005
DOI: 10.1038/sj.onc.1208387
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive characterization of HNPCC-related colorectal cancers reveals striking molecular features in families with no germline mismatch repair gene mutations

Abstract: A considerable fraction of families with HNPCC shows no germline mismatch repair (MMR) gene mutations. We previously detected 'hidden' MMR gene defects in 42% of such families, leaving the remaining 58% 'truly' mutation negative. Here, we characterized 50 colorectal carcinomas and five adenomas arising in HNPCC families; 24 truly MMR gene mutation negative and 31 MMR gene mutation positive. Among 31 tumors from MMR gene mutation positive families, 25 (81%) had active Wnt signaling as indicated by aberrant b-ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
87
9

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 80 publications
(106 citation statements)
references
References 40 publications
9
87
9
Order By: Relevance
“…Recurrent gains affected chromosomes 17 and 19, though these regions are too large to allow distinction of potential target genes (Table II). The stable genetic profiles demonstrated in the HNPCC associated ovarian cancers are in line with the findings in colorectal cancer, in which tumors with germline MMR gene mutations or MLH1 promotor methylation display near diploid genetic profiles with few structural changes (30)(31)(32). STAC analysis was applied to the different tumor subsets in order to identify target genes within the regions specifically gained or lost (Table IV).…”
Section: Discussionsupporting
confidence: 65%
“…Recurrent gains affected chromosomes 17 and 19, though these regions are too large to allow distinction of potential target genes (Table II). The stable genetic profiles demonstrated in the HNPCC associated ovarian cancers are in line with the findings in colorectal cancer, in which tumors with germline MMR gene mutations or MLH1 promotor methylation display near diploid genetic profiles with few structural changes (30)(31)(32). STAC analysis was applied to the different tumor subsets in order to identify target genes within the regions specifically gained or lost (Table IV).…”
Section: Discussionsupporting
confidence: 65%
“…27,36 Although Abdel-Rahman et al reported only 54% of 20q gain in MMR-proficient familial CRC, this was found in almost all tumors that showed abnormalities. 35 When compared with the 20q gain frequency in a series of sporadic rectal carcinomas (36%), which was previously analyzed using the same methodology, we found that the frequency of 20q gain is significantly higher in MMR-proficient familial CRC (p ¼ 3.4 Â 10 À3 ) as compared with the rectal cancers, which rarely show MMR-deficiency. 27 The choice of the CRC series to compare 20q gain is critical.…”
Section: Gain Of Chromosome 20qmentioning
confidence: 61%
“…In addition, half of the MMR-proficient familial CRCs displayed less than five aberrations. 35 To compare our results with this earlier study, we counted the number of copy number aberrations (excluding cnLOH) in our series. In our series of MMR-proficient familial CRCs, there was on average 7.5 copy number aberrations per carcinoma, and we observed fewer than five copy number aberrations in 30% (9/30) of the CRCs.…”
Section: Snp Array Profilingmentioning
confidence: 82%
“…42 Comparative genomic hybridization studies suggest that FCCTX tumors typically harbor 6-8 copy number alterations with recurrent gains of 7p, 7q, 8q, 13q, 20p, and 20q and losses of 17p, 18p, and 18q. 62,63 Gain of the 20q region has been specifically linked to FCCTX tumors and several candidate target genes such as 'GNAS (GNAS complex locus),' 'AURKA (aurora kinase A),' 'SRC (v-src avian sarcoma (Schmidt-Ruppin A-2) viral oncogene homolog),' 'TOP1 (topoisomerase (DNA) I),' 'NELFCD (negative elongation factor complex member C/D),' 'ADRM1 (adhesion regulating molecule 1),' 'ASIP (agouti signaling protein),' 'CDH26 (cadherin 26),' and 'HNF1A (HNF1 homeobox A)' reside herein (Figure 3). 24,62,63 GNAS promotes proliferation through activation of the Wnt and ERK1/2 MAPK signaling pathways.…”
mentioning
confidence: 99%
“…62,63 Gain of the 20q region has been specifically linked to FCCTX tumors and several candidate target genes such as 'GNAS (GNAS complex locus),' 'AURKA (aurora kinase A),' 'SRC (v-src avian sarcoma (Schmidt-Ruppin A-2) viral oncogene homolog),' 'TOP1 (topoisomerase (DNA) I),' 'NELFCD (negative elongation factor complex member C/D),' 'ADRM1 (adhesion regulating molecule 1),' 'ASIP (agouti signaling protein),' 'CDH26 (cadherin 26),' and 'HNF1A (HNF1 homeobox A)' reside herein (Figure 3). 24,62,63 GNAS promotes proliferation through activation of the Wnt and ERK1/2 MAPK signaling pathways. 64 Activating missense mutations in GNAS have been demonstrated in sporadic colorectal cancer, but the GNAS c.601G4T hot spot mutation could not be identified in a study of FCCTX tumors.…”
mentioning
confidence: 99%